PENGARUH PERBANDINGAN GULA PUTIH DENGAN GULA MERAH DAN PENAMBAHAN SANTAN TERHADAP MUTU ABON JAMUR TIRAM (The Effect of Ratio of White Sugar with Brown Sugar and Coconut Milk Addition on the Quality of Shredded Oyster Mushrooms) - Winda Widyastuti; Terip Karo-Karo; Linda Masniary Lubis (Universitas Sumatera Utara, 2017)
ABSTRACT The research was purposed to find the effect of ratio of white sugar with brown sugar and coconut milk addition on the quality of shredded oyster mushrooms. This research was conducted at Laboratory of Food Technology, Faculty of Agriculture, University of North Sumatera, Medan, using completely randomized design with two factors, i.e ratio of white sugar with brown sugar (G) : (100% : 0%, 75% : 25%,50% : 50%, 25% : 75%, 0% : 100%) and coconut milk addition (S) : (10%, 20%, 30%). Parameters analyzed were water content, ash content, protein content, fat content, crude fiber content, organoleptic of score and hedonic of color, flavor, taste, and texture. The results showed that the ratio of white sugar with brown sugar and coconut milk addition had highly significant effect on water content, ash content, score of color, score of texture, hedonic of color, hedonic of taste. The coconut milk addition had highly significant effect on water content, fat content, score of color, score of flavor, score of taste, hedonic of color, hedonic of taste.The interaction of the two factors had significant effect on score and hedonic of color. The ratio of white sugar with brown sugar of 25% : 75% and coconut milk addition of 10% produced the best quality of shreddedoyster mushrooms. Keyword : shredded oyster mushrooms, brown sugar, white sugar, coconut milk ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh perbandingan gula putih dengan gula merah dan penambahan santan terhadap mutu abon jamur tiram. Penelitian ini dilakukan di Laboratorium Teknologi Pangan, Fakultas Pertanian, Universitas Sumatera Utara, Medan, menggunakan rancangan acak lengkap (RAL) dengan 2 faktor yaitu perbandingan gula putih dengan gula merah (G) : (100% : 0%, 75% : 25%, 50% : 50%, 25% : 75%, 0% : 100%) dan penambahan santan (S) : (10%, 20%, 30%). Parameter yang dianalisis adalah kadar air, kadar abu, kadar protein, kadar lemak, kadar serat kasar, organoleptik skor dan hedonik warna, aroma, rasa, dan tekstur. Hasil penelitian menunjukkan bahwa perbandingan gula putih dengan gula merah memberikan pengaruh berbeda sangat nyata terhadap kadar air, kadar abu, nilai skor warna, skor tekstur, hedonik warna, dan hedonik rasa. Penambahan santan memberikan pengaruh berbeda sangat nyata terhadap kadar air, kadar lemak, nilai skor warna, nilai skor aroma, nilai skor rasa, nilai hedonik warna, nilai hedonik rasa. Interaksi antara kedua faktor memberikan pengaruh berbeda nyata terhadap nilai skor warna dan nilai hedonik warna. Perbandingan gula putih dengan gula merah 25% : 75% dan penambahan santan 10% menghasilkan mutu abon jamur tiram terbaik. Kata Kunci : Abon jamur tiram, gula merah, gula putih, santan.